Sensor Performance Test of Laboratory Type Silage Production, Data Acquisition and Control System; Module-B - Fulya TAN; Figan DALMIS; Ersen OKUR; Ibrahim Savas DALMIS (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The main objective of this study is to investigate the performance of the sensors integrated into the laboratory-type silage production, data acquisition and control system. The system developed within the scope of the TUBITAK 1002 project, is a PLC (Programmable Logic Controller)-controlled multi-sensor data acquisition-based designed to carry out numerous studies to improve silage quality. The system comprises chopping, weighing, ensiling, data acquisition and control units. The ensiling unit consists of two modules, module-A (compaction principle) and module-B (vacuum principle). This research focuses on measurements conducted with plexiglass silos (24.5 cm3) in the module-B unit. Plexiglass silos were equipped with an oxygen sensor (±0-100 %), carbon dioxide sensor (0-5000/40 000 ppm), temperature sensor (±0.53 °C, -10 – 80 °C), humidity sensor (0-100 %), pH sensor (2-12), and pressure sensor (± 1000 mbar). The data received from the sensors were recorded in the data acquisition unit at the rate of one data per second. Due to the large amount of data acquired, average values were used. The data are displayed on the screen of the HMI operator panel, designed using the GOP HMI editor software, and are stored in Excel form. The measurements were conducted during the silage (aerobic) and post-silage (anaerobic) periods. According to the research results, the temperature ranged from 15-30°C, the humidity content ranged from 60-98%, the pH content ranged from 5.8 to 4.3, the oxygen(O2) content ranged from 8.0 to 0 mmol/L, and the carbon dioxide(CO2) level ranged from 0 to 40 mmol/L.